Diálogos culturales : imaginarios nacionales : viajes, territorios e identidades - Traverso, Ana; Kottow, Andrea (RiL editores, 2016)
In the seventh version of the meeting, the challenge of meeting the possibility of thinking was the "national imaginary" from its territorial configurations, geographic, geopolitical, cultural and identity, among others. Specialists in the areas of literature and anthropology discussed literary discourses, stories and oral histories of modernity, very different geographical, historical and cultural background. The contribution of these dialogues is the breakdown of static meanings that seem to have terms like center and periphery, city and province, modernity and delay and/or knowledge and ignorance, thus contributing to the nature of these concepts and review them again with more critical eyes.